Environmental management practices and financial performance: evidence from large listed Indian enterprises. Issue 1 (2nd January 2022) - Kumar, Surender; Dua, Pritika
Abstract : Large enterprises have been at the forefront of environmental management with active participation in industrywide programs and adoption of a 'beyond compliance' approach. The present study revisits the premise of environmental–financial linkage in an Indian context with a focus on large listed enterprises. We develop a comprehensive dataset of 459 large listed Indian companies covering major manufacturing and service sectors of the economy over an eleven-year period from 2008–09 to 2018–19. Static and dynamic regression models are used to gauge the impact of environmental management practices on firm profitability (Return on Assets and Return on Equity) and market valuation ( Tobin Q, Market to Book Value Ratio and Excess Valuation to sales ratio). Empirical results suggest a positive impact of environmental management on firm profitability and market valuation. These results are of interest to corporate and policy makers for recognizing the financial implications of corporate environmental management.